The psychosocial dimensions of fatigue in men treated for prostate cancer. Issue 1 (28th August 2015) - McConkey, Robert W.
ABSTRACT: Prostate cancer is one of the most prevalent forms of cancer in men worldwide. Cancer‐related fatigue (CRF) is the most frequently reported side effect of all cancer treatments and occurs in up to 74% of men treated for prostate cancer, particularly those receiving combined hormone and radiation therapies. Patients report the devastating impact of CRF on their quality of life and psychosocial functioning, affecting work, social, emotional and cognitive performance. It can manifest during treatment and persist long after its completion. A diagnosis of CRF is achieved once all other treatable factors such as anaemia or anxiety and depression have been managed, but does not alleviate the fatigue. The Functional Assessment of Cancer Therapy‐Fatigue (FACT‐F) is a brief and easily administered valid and reliable tool recommended for the assessment of CRF. Non‐pharmacological interventions such as activity‐based programs and psychosocial interventions including prostate cancer specific education and cognitive behavioural therapy have shown benefits in reducing levels of CRF. A multidisciplinary approach to the management of CRF in prostate cancer patients is advocated. The NICE four‐tier model of psychological support can be used as a framework to assist nurses and other health care professionals to alleviate the psychosocial burden of CRF. More research studies using a solid methodological foundation are required in men with prostate cancer to provide robust evidence which can be applied in practice.